1970
DOI: 10.1084/jem.131.6.1169
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Antibodies With Either Identical or Unrelated Individual Antigenic Specificity During Repeated Immunizations With Streptococcal Vaccines

Abstract: Electrophoretically monodisperse antibody components in rabbit antisera to the carbohydrates of the Groups A and C streptococci have been examined for their individual antigenic specificity. In these antibody components which were isolated by preparative electrophoresis, individual antigenic specificity was confined to the specific antibody and was absent in the nonantibody γ-globulin. Radioprecipitation experiments and the use of immune absorbent columns constructed from goat anti-antisera, which had been abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
6

Year Published

1971
1971
1981
1981

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 30 publications
2
18
0
6
Order By: Relevance
“…The only exception was antiserum BS-4432, where the major clonotype (isoelectric point 6.1) did not bind Av-CHO. Similar observations were previously reported showing that dominant clonotypes elicited by immunization with streptococcal vaccines are not always group polysaccharide-specific antibodies (24,25). It ap- pears that a substantial number of clonotypes expressed at a low quantitative level exhibited a high antigen binding capacity, for example, the dominant clonotype of BS-4433 (pH 6.7-7.0) was compared with the discrete clonotype focusing at pH 7.5-7.9.…”
Section: Response Patterns Of Basilea Rabbits To the Streptococcal Avsupporting
confidence: 84%
“…The only exception was antiserum BS-4432, where the major clonotype (isoelectric point 6.1) did not bind Av-CHO. Similar observations were previously reported showing that dominant clonotypes elicited by immunization with streptococcal vaccines are not always group polysaccharide-specific antibodies (24,25). It ap- pears that a substantial number of clonotypes expressed at a low quantitative level exhibited a high antigen binding capacity, for example, the dominant clonotype of BS-4433 (pH 6.7-7.0) was compared with the discrete clonotype focusing at pH 7.5-7.9.…”
Section: Response Patterns Of Basilea Rabbits To the Streptococcal Avsupporting
confidence: 84%
“…Previous studies from this laboratory have shown that uniform antibodies to the streptococcal carbohydrates possess IAS (4), and that in a single rabbit, antibodies with identical IAS recur with repeated inlmunizations over an 18 month period (38), despite their absence during the interval between immunizations.…”
Section: Resultsmentioning
confidence: 99%
“…The finding furthermore suggests that antibodies against the streptococcal Group A-variant antigen may be taken from a rare subpopulation. Persistence of Idiotypic Antibodies.--In an earlier experimental series, the restimulation of monoclonal antibodies specific for the streptococcal Groups A-CHO and C-CHO was magnified during a secondary course of immunization (40). This aspect was reinvestigated for 15 homogeneous Group Av-CHOspecific antibodies by analytical IEF and for K429-1 Ab, K429-7s Ab, and K6-89 Ab by both IEF and use of anti-idiotypic antisera.…”
Section: Hemagglutination Inhibition Analysis --Hemagglutination Inhmentioning
confidence: 99%